1999
DOI: 10.1055/s-1999-9895
|View full text |Cite
|
Sign up to set email alerts
|

CT-gesteuerte perkutane Biopsien zur Klassifizierung von fokalen Leberläsionen: Vergleich zwischen 14 G- und 18 G-Stanzbiopsienadeln

Abstract: CT-guided biopsy of hepatic lesions with the 18-g biopsy needle is of equivalent diagnostic accuracy when compared with the 14-g needle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…Most patients with HCA are young, with minor symptoms on malignant progression; invasive procedures should preferably be avoided. While the risk of bleeding complications is very low when using an 18G core needle biopsy (0.6%) [ Haage et al 1999 ; Kadri Aribas et al 2010 ; Aribas et al , 2012 ], the risks are not negligible, and deaths due to bleeding complications have been reported [ Stattaus et al 2007 ]. In our practice a biopsy has not been performed to date, except where the diagnosis of a specific adenoma subtype was expected to alter clinical management.…”
Section: Biopsy In the Management Of Hcamentioning
confidence: 99%
“…Most patients with HCA are young, with minor symptoms on malignant progression; invasive procedures should preferably be avoided. While the risk of bleeding complications is very low when using an 18G core needle biopsy (0.6%) [ Haage et al 1999 ; Kadri Aribas et al 2010 ; Aribas et al , 2012 ], the risks are not negligible, and deaths due to bleeding complications have been reported [ Stattaus et al 2007 ]. In our practice a biopsy has not been performed to date, except where the diagnosis of a specific adenoma subtype was expected to alter clinical management.…”
Section: Biopsy In the Management Of Hcamentioning
confidence: 99%
“…On careful review of the literature, however, we noted that there is no universal agreement whether different needle sizes do affect diagnostic yield or not. For example, in biopsies of focal hepatic lesions, one study compared the results of biopsy in 268 patients and reported similar results for 18-and 14-gauge needles [12]. On the other hand, another study on 163 patients reported a significantly higher diagnostic yield for 16-gauge compared to 18-gauge needles [13].…”
Section: Discussionmentioning
confidence: 98%
“…Seither konnte sich das Verfahren als komplikationsarme und genaue Methode zur Gewebeentnahme neben der Sonographie in der klinischen Routine durchsetzen und bietet den Vorteil der überlagerungsfreien, artefaktarmen und reproduzierbaren Darstellung der Läsion und benachbarter eventuell vulnerabler Strukturen [2,3]. In der Planungsschicht ist die exakte Bestimmung des Punktionsortes, des Einstichwinkels und der Einstichtiefe möglich.…”
Section: Schlüsselwörter: Biopsie ± Computertomographie ± Zielgerätunclassified